Electrodeposition of polymer nanodots with controlled density and their reversible functionalization by polyhistidine-tag proteins - Bazin, Damien (Langmuir : the ACS journal of surfaces and colloids, 2012)
We present a simple and rapid procedure for producing polymer-coated substrates that can be easily functionalized by ion-chelating proteins. The procedure consists of depositing 18 nm metal-chelating cyclam-modified polymer nanoparticles (cyclam-nps) onto a conductive substrate (an Indium Tin Oxide (ITO) electrode) from an aqueous dispersion of Cu(2+)-loaded cyclam-nps while being subjected to a direct current (DC) field. The density of deposited nps as measured by AFM is shown to be in direct correlation to the concentration of nps in the dispersion with deposition of the particles taking less than 5 s. Because of the functionalization of the nps with cyclam groups, they can be used as anchoring sites for 6-Histidine (6-His) tagged proteins through complexation with divalent metal ions. In this work 6-His Green Fluorescent Protein (6-His GFP) is used as a model protein. The characterization by fluorescence microscopy clearly shows that the protein affinity was ion dependent and that the 6-His GFP density can be controlled by np density, which is itself easily tunable. AFM observations confirmed the immobilization of 6-His GFP onto cyclam-nps and its subsequent removal by treatment with ethylenediaminetetraacetic acid (EDTA)